Upaya Meningkatkan Motivasi Belajar IPA melalui Model Pembelajaran Quantum Teaching di Kelas V SDI Tabene (Aljabar : Jurnal Ilmuan Pendidikan, Matematika dan Kebumian, 2025)
Improving students' learning motivation in Natural Sciences (IPA) in fifth grade students of SDI Tabene through the application of the Quantum Teaching learning model. The Quantum Teaching learning model, with the TANDUR principle (Grow, Experience, Name, Demonstrate, Repeat, Celebrate), is designed to create a fun and relevant learning environment to students' experiences. This Classroom Action Research was carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects of the study were 32 fifth grade students of SDI Tabene. Data were collected through observation, tests, and documentation. The results showed an increase in students' learning motivation. In cycle I, the average student learning motivation was 60.7%, which was classified as sufficient. After improvements were made in cycle II by optimizing each stage of TANDUR, the average student learning motivation increased to 82.1%, classified as very good. This increase was seen from students' higher enthusiasm, active participation in discussions, and increased curiosity about science materials. It can be concluded that the application of the Quantum Teaching learning model is effective in improving students' learning motivation in fifth grade students of SDI Tabene.